An emergency supply test for another oil crisis - Mathias Lefeldt (Intereconomics, 1979)
In the spring of 1978 the International Energy Agency (IEA) staged the second “Allocation System Test”, a simulation exercise designed to check the ability of 19 OECD countries to cope jointly with another oil crisis. The topicality of such a contingency test is demonstrated by the disturbances in Iran. The following article sheds light on the motives, objectives and mechanisms of the IEA concept. *** DIRECT SUPPORT *** A02GP001 00004
Keywords: 330; Energy Policy